Is the Debt Waiver Scheme a Right Solution to Farmers Suicide? - Pooja (Innovative Research Thoughts, 2017)
As per the estimates revealed by Central Statistics office the total share of Agriculture and Allied sectors in terms of GDP is 13.9% during 2015-16, where more than 48.9% of India’s population depend on Agricultural sector. Farmers risk in his occupation varies from small, marginal and large farmer’s from one village to another, one district to another and one state to another state. But the policies framed by the central government remains to be the same irrespective of changes in the amount and extent to which the risk is taken by the individual farmer. Moreover the outreach of the scheme is not for the affected farmers on one side and on another side prompt loan payers show regret for this scheme. One such scheme introduced by the Government is the Debt Waiver Scheme. Is this scheme really useful to the farmers? Or is there any other probable solution for the problems being faced by farmers?